Vascular endothelial growth factor-B: Impact on physiology and pathology. Issue 3 (4th May 2018) - Zhu, Hongyu; Gao, Mingming; Gao, Xiangdong; Tong, Yue
ABSTRACT: Angiogenesis plays an important role in controlling tissue development and maintaining normal tissue function. Dysregulated angiogenesis is implicated in the pathogenesis of a variety of diseases, particularly diabetes, cancers, and neurodegenerative disorders. As the major regulator of angiogenesis, the vascular endothelial growth factor (VEGF) family is composed of a group of crucial members including VEGF-B. While the physiological roles of VEGF-B remain debatable, increasing evidence suggests that this protein is able to protect certain type of cells from apoptosis under pathological conditions. More importantly, recent studies reveal that VEGF-B is involved in lipid transport and energy metabolism, implicating this protein in obesity, diabetes and related metabolic complications. This article summarizes the current knowledge and understanding of VEGF-B in physiology and pathology, and shed light on the therapeutic potential of this crucial protein.